A Rare Presentation of Nocardia pericarditis Leading to Cardiac Tamponade in an Immunocompetent Patient - Faircloth, Erika L (Cureus, 2019)
Nocardia can cause isolated disease in many parts of the body including the brain, skin, and lungs. It is also capable of causing disseminated disease. In almost all cases, Nocardia infections occur in immunocompromised hosts with depressed cell-mediated functions. We present a case of disseminated Nocardia farcinica leading to pericardial effusion and tamponade in an immunocompetent host with the only risk factor being heavy alcohol intake. Treatment relies on an accurate diagnosis. This case presentation highlights the importance of considering Nocardia infections in an alcoholic patient with a worsening clinical picture.